2022
DOI: 10.21203/rs.3.rs-1687679/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimates of prevalence of anti-SARS-CoV-2 antibodies among blood donors in South Africa in March 2022

Abstract: In line with previous instalments of analysis from this ongoing study to monitor ‘Covid Seroprevalence’ among blood donors in South Africa, we report on an analysis of 3395 samples obtained in mid-March 2022 from all provinces of South Africa – a timepoint just after the fourth (primarily omicron) wave of infections. As in our previous analyses, we see no evidence of age and sex dependence of prevalence, but significant variation by race. Differences between provinces have largely disappeared, as prevalence ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 6 publications
5
32
0
Order By: Relevance
“…Nonetheless, our findings need to be interpreted in the context of South African SARS-CoV-2 epidemiology with progressively increasing seroprevalence due to prior infection (mostly undiagnosed) and/or vaccination (Bingham et al, 2022, Madhi et al, 2022, Sun et al, 2022). For example, among blood donors, after the BA.1 wave the estimated national prevalence of anti-nucleocapsid antibodies was 87% (indicating previous infection) with a further 10% having anti-spike antibodies only (suggesting vaccination without prior infection) (Bingham et al, 2022). Indeed, our finding that the aHR shifted towards a lower risk of severe outcomes during BA.4/BA.5 vs. BA.1 in models not accounting for vaccination and prior diagnosed infection, suggests that the observed continued ecologic decoupling of COVID-19 cases and severe outcomes is at least partly due to growing protection against severe disease from both prior infection and vaccination.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nonetheless, our findings need to be interpreted in the context of South African SARS-CoV-2 epidemiology with progressively increasing seroprevalence due to prior infection (mostly undiagnosed) and/or vaccination (Bingham et al, 2022, Madhi et al, 2022, Sun et al, 2022). For example, among blood donors, after the BA.1 wave the estimated national prevalence of anti-nucleocapsid antibodies was 87% (indicating previous infection) with a further 10% having anti-spike antibodies only (suggesting vaccination without prior infection) (Bingham et al, 2022). Indeed, our finding that the aHR shifted towards a lower risk of severe outcomes during BA.4/BA.5 vs. BA.1 in models not accounting for vaccination and prior diagnosed infection, suggests that the observed continued ecologic decoupling of COVID-19 cases and severe outcomes is at least partly due to growing protection against severe disease from both prior infection and vaccination.…”
Section: Discussionmentioning
confidence: 87%
“…Although we did not compare BA.4/BA.5 with BA.2 directly as BA.2 did not cause a distinguishable surge in infections in the Western Cape, disease severity of BA.2 and BA.1 are similar (Lewnard et al, 2022) and we found no evidence of worse clinical outcomes with BA.4/BA.5 compared to BA.1. Nonetheless, our findings need to be interpreted in the context of South African SARS-CoV-2 epidemiology with progressively increasing seroprevalence due to prior infection (mostly undiagnosed) and/or vaccination (Bingham et al, 2022, Madhi et al, 2022, Sun et al, 2022). For example, among blood donors, after the BA.1 wave the estimated national prevalence of anti-nucleocapsid antibodies was 87% (indicating previous infection) with a further 10% having anti-spike antibodies only (suggesting vaccination without prior infection) (Bingham et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…However, in our study, this increased pathogenicity did not translate into clinical severity. Recent national seroprevalence data among healthy blood donors post the BA.1 fourth wave in South Africa showed that 97% of individuals had SARS-CoV-2 antibodies, with 87% due to prior infection and an additional 10% due to vaccination alone 15 . This extremely high population immunity, and speci cally the elicited T-cell responses, could explain the continuing low severity observed despite the emergence of additional Omicron lineages with increased transmissibility and immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of seroepidemiological studies have been performed to date in the general population extending into the Omicron wave. 4-6 The proportion of infected individuals has dramatically increased following the surge of the Omicron sub-lineages, due to their increased transmissibility and escape from vaccine or infection-induced immunity. 15 Moreover, as the percentage of Omicron-infected paucisymptomatic or asymptomatic individuals appears to be high, the number of underreported infections that are not captured by community surveillance systems may be significantly greater.…”
Section: Discussionmentioning
confidence: 99%
“…A few serosurvey studies have been reported involving the general population and extending into the Omicron wave; 4-6 these studies provide valuable information on the extent of transmission in the past and contribute towards understanding the future course of the pandemic and to shaping public health decision making. Here, as part of the ProVaVac Valencian COVID-19 vaccine research program launched by the VC government in March 2021, we conducted a population-based study aimed primarily at estimating the cumulative incidence of SARS-CoV-2 infection in the general VC population after the surge and spread of the Omicron BA.1 variant.…”
Section: Introductionmentioning
confidence: 99%